Stretchable Electronics: Direct Transfer of Magnetic Sensor Devices to Elastomeric Supports for Stretchable Electronics (Adv. Mater. 8/2015). (February 2015) - Melzer, Michael; Karnaushenko, Daniil; Lin, Gungun; Baunack, Stefan; Makarov, Denys; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> The inside front cover highlights the breakthrough from rigid silicon‐based magnetoelectronic devices to soft and compliant ones. On page 1333, M. Melzer, D. Makarov, and co‐workers describe a method to transfer entire magnetoresistive microsensor structures from a rigid silicon substrate to a pre‐stretched rubber membrane in a single step. This fabrication route overcomes several limitations of previous approaches to compliant magnetoelectronics and allows for invariance versus stretching up to 30%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>